A preliminary study on detection of periodontal pathogens from saliva samples of selected Sarawakian - Cheng Siang, Tan; Grace, Bebey; Elexson, Nillian; Azham, Zulkharnain; Nurshaline, Pauline Haji Kipli4 (Malaysian Society for Microbiology, 2021)
Aims: The oral cavity has the most complex microbiota after the stomach. A disturbed oral equilibrium can lead to the onset and development of periodontal disease. The known causative agents are the red complex bacteria (Porphyromonas gingivalis, Tannerella forsythia, Treponema denticola). This study was carried out to provide insights on the prevalence of periodontal pathogens in Sarawakian oral cavity since the data at present is still lacking. Methodology and results: A total of two millilitres (2 mL) of saliva samples were collected from twenty-seven (n=27) individuals (21 gingivitis, 6 healthy) between aged 18 until 30 years old, from Sarawak General Hospital. DNA extraction for the saliva samples was done by using phenol-chloroform method. Then, 16S rRNA PCR was performed followed by species-specific PCR for red complex bacteria detection. Statistical data was analysed using GraphPad Prism 8.4.1 software. As a result, 14% of gingivitis-affected female subjects were found with all the member of red complex species. Co-occurrence of red complex species was observed but no significant difference was found. An alarming presence of red complex bacteria particularly T. forsythia was detected in 57% of gingivitis subject as compared to the other red complex species. Conclusion, significance and impact of study: The risk of acquiring periodontal disease increases by having at least one of the red complex species in the oral environment. Therefore, the rapid molecular detection of red complex bacteria in this study is useful for risk assessment of periodontal disease and proper species-targeted treatment to patients especially Sarawakian in general as the result has shed lights to the fairly poor oral status of volunteers.